FEMALE JEWELLERY OF THARU AND BUXA TRIBE OF UTTARAKHAND - Bhatt, Pooja; Rani, Anita; Gahlot, Manisha (International Journal of Research -GRANTHAALAYAH, 2018)
India is marked by its rich traditional heritage of tribal/folk arts and culture. Since the days of remote past, the diversified art & cultural forms generated by the tribal and rural people of India have continued to evince their creative magnificence. Apart from their outstanding brilliance from the perspective of aesthetics, the tribal/folk art and culture forms have played an instrumental role in reinforcing national integrity, crystallizing social solidarity, fortifying communal harmony, intensifying value-system and promoting the elements of humanism among the people of the country. India has been endowed with a rich tribal culture, which despite modernisation has kept its unique traditions and values intact. Tribal Jewellery still bears a definite earthy charm. On the other hand, being different from the conventionally manufactured jewellery items, the rarity of ethnic jewellery is cherished by many. In the present study documentation of the tharu and buxa jewellery was done, and many similarities were observed.